Hypochondriacal delusion in an elderly woman recovers quickly with electroconvulsive therapy - Annemieke Dols; Didi Rhebergen; Piet Eikelenboom; Max L. Stek (Clinics and Practice, 2012)
A 72-year-old woman without any medical and psychiatric history, suffered from nausea, pain in the epigastria and constipation for over a year. She eventually lost 20 kilograms despite nightly drip-feeding. Extensive additional tests did not reveal any clues for her complaints. She remained convinced that her symptoms were a side-effect of anti-fungal medication she used. She was diagnosed with hypochondria. In the course of time her ideas about her somatic symptoms became delusional and she was diagnosed with a hypochondriacal delusion as part of melancholia, without depressed mood or loss of interest or pleasure as prominent features. It is important to recognize melancholia as soon as possible by continually evaluating other symptoms of depression. This may enable to avoid repetitive and exhaustive somatic examinations, which are not indicated, and to start effective treatment. In our patient electroconvulsive therapy resulted in a fast and complete recovery.